IMPLEMENTASI SISTEM INFORMASI MANAJEMEN KEPEGAWAIAAN (SIMPEG) DI KANTOR KEMENTERIAN AGAMA KABUPATEN MALUKU TENGAH - Tuanany, Rusli (Patria Artha University, 2021)
This study aims to determine the implementation of the Personnel Management Information System (SIMPEG) at the Office of the Ministry of Religion of Central Maluku Regency and to find out what obstacles arise in implementing the SIMPEG. This research is descriptive using a qualitative approach so that to support this research activity, data collection from informants is carried out. Data analysis is preceded by collecting and collecting data or information in the field, after that it is classified according to the type and group, then it is analyzed or interpreted qualitatively. Based on the results of the analysis, it is known that the implementation of SIMPEG has made a major contribution to the implementation of the functions of the Ministry of Religion Office of Central Maluku Regency, but in implementing SIMPEG it can be said that it is not optimal, because it is still experiencing several obstacles and problems caused by several shortcomings in its implementation.